Reality and perspective of instrumental diagnostics hemostasis system functional state in critical medicine - M. N. Shpisman; I. I. Tyutrin; V. V. Udut; Ye. G. Ripp; V. O. Sorokozsherdiyev (Бюллетень сибирской медицины)
In article to discuss diagnostic value of blood aggregate regulation system (BARS) and complexity of diagnostics, particularly, in critical state.Advantages and disadvantages of instrumental diagnostics technique were analyzed: thromboelastographia and lowfrequency piezoelectric hemocoagulographia of whole blood. Estimates new next-generation instrumental method of research - lowfrequency contact conductometry. This method permits to evaluate role blood plasma, cells hemostasis factors and wall of vessels in critical state BARS dysfunction.